Perilaku Konsumtif Mahasiswa Gen Z Pengguna TikTok Shop: Analisis Perspektif Maqashid Syariah - Mawarni, Iga; Fahrurrozi; Muhtadi, Ridan (Kartika: Jurnal Studi Keislaman, 2025)
Tiktok Shop is one proof of increasingly sophisticated technological developments in the realm of buying and selling online. But behind the advantages offered, there are still things that are detrimental to the community, namely buying an item that is only based on wishes not only for daily needs. This study aims to determine the consumptive behavior of Muslim students in Madura as Z Gen in using the Tiktok Shop application while looking based on the perspective of Sharia Maqashid. This study uses qualitative methods with descriptive forms. The data collection techniques used are observations, interviews, and literature reviews. There are three criteria for determining the informant used: First, Muslim students in Madura; Second, students who have Tiktok applications; Third, have bought goods in the Tiktok Shop application. The results showed the occurrence of consumptive behavior because it was caused by several internal and external factors, namely: 1) Internal factors: Age and lifestyle, 2) External factors: free postage vouchers, discount vouchers, and cheaper prices. These factors, if viewed based on the perspective of Sharia Maqashid, Muslim students in Madura in buying an item not based on the level of priority and do not refine the principle of hifz an-nafs (maintaining the soul) and Hifz al-Mal (maintaining property) because it is influenced and controlled by a desire for pleasure and not based on needs, resulting in consumptive behavior